Design Digital Twin Technology for Practicum Distance Learning - Hari Anna Lastya; Sadrina Sadrina; Muhammad Ikhsan; Fashbir Is (Jurnal Penelitian Pendidikan IPA, 2025)
One effective way to carry out laboratory practicums remotely is by using digital twin technology. This study investigates the feasibility and user response to using digital twin technology for remote Basic Electrical Energy practicums. This study employs a Research and Development (R&D) method involving students from the Department of Electrical Engineering. A validation sheet and a questionnaire were used to assess feasibility and user responses, respectively. The feasibility results of digital twin technology for remote practicums according to media experts obtained. The feasibility test achieved 90.71% from material experts and 91.43% from media experts from media experts, categorizing the system as "highly feasible." User responses were also positive, with scores of 88.25% for material presentation, 87% for the learning process, and 86.75% for practicality. The overall percentage across all indicators was 87.33%, placing it in the “Very Good” category for use in the Basic Electrical Energy Practicum.